Madelung’s disease – progressive, excessive, and symmetrical deposition of adipose tissue in the subcutaneous layer: case report and literature review - Szewc M (Dove Medical Press, 2018)
Monika Szewc,1 Robert Sitarz,1–3 Nina Moroz,2 Ryszard Maciejewski,1,* Ryszard Wierzbicki2,4,* 1Department of Human Anatomy, Medical University of Lublin, Lublin, Poland; 2Department of Surgery with Trauma, Orthopaedic and Urological Subunit, Independent Public Health Care Center of the Ministry of Interior and Administration in Lublin, Lublin, Poland; 3Department of Surgery, St John’s Cancer Center, Lublin, Poland; 4Department of Surgical Oncology, Medical University of Lublin, Lublin, Poland *These authors contributed equally to this work Abstract: Madelung’s disease is a rare disorder described for the first time in the year 1846 by Brodie. It is characterized by the occurrence of progressive, excessive, and symmetrical deposits of adipose tissue in the subcutaneous layer. Most often, these changes concern the neck, the nape of the neck, arms, and upper back, giving the patients a specific, pseudoathletic appearance. Madelung’s disease is also known as multiple symmetrical lipomatosis, benign symmetrical lipomatosis, and Launois-Bensaude syndrome. The most commonly affected ones are men who drink alcohol in excessive amounts. The fat masses emerging in the course of the disease are painless but can lead to adverse repercussions. Patients may experience dysphagia, dysphonia, difficulty in breathing, and limited mobility of the neck. The reasons for the willingness to take up treatment are also often esthetic reasons. The disease is usually accompanied by numerous metabolic disorders. The etiology of the disease has not been sufficiently explained so far, which creates diagnostic and therapeutic difficulties. Currently used treatment is limited to surgical resection of the resulting lesions or liposuction. Unfortunately, the effectiveness of these activities is limited. Most patients experience recurrence after treatment. This paper discusses the essence of Madelung’s disease, numerous aspects of etiology, the manner of diagnosis, and treatment based on current literature data. Keywords: Madelung’s disease, lipomatosis, multiple symmetrical